O percurso histórico da improvisação no ragtime e no choro - Albino, César [UNESP]; Lima, Sonia R. Albano de [UNESP] (Escola de Música da UFMG, 2011)
O artigo teve como objetivo investigar em que medida a improvisação e a tradição oral permitiram a consolidação do ragtime e do choro em gêneros musicais com aceitação popular na virada do século XIX. A escolha concentrou-se nas semelhanças formais existentes entre ambos e nos caminhos percorridos por ambos para essa consolidação. A partir dos conceitos de territorialização e desterritorialização criados por Gilles Deleuze e Félix Guattari, incorporados à improvisação musical por Rogério Costa, verificamos o tipo de improvisação utilizado nesses dois gêneros. O relato histórico reafirma a ideia de D. Bailey de que a improvisação está sempre presente na criação de novos sistemas notacionais, gêneros e estilos musicais, ainda que nos processos de transmutação, ela saia de cena. O texto é parte da dissertação de mestrado defendida no IA-UNESP.

This study aims at investigating to what extent improvisation and oral tradition allowed for the consolidation of ragtime and choro into musical genres which became popular in the turning of the nineteenth century. The choice was concentrated on the formal similarities existing between both kinds of music and in the paths taken by both of them in their process of consolidation. As far as the concepts of territorialization and de-territorialization coined by Gilles Deleuze and Félix Guattari, and incorporated in musical improvisation by Rogério Costa, it was possible to verify the type of improvisation used in these two genres. Historically, it re-states D. Bailey's idea that improvisation is always present in the creation of new notational systems, genres and musical styles, even if it leaves the scene during the transmutation processes. This article derives from the first author's Master of Arts dissertation (IA-UNESP, Brazil).
The historical path of improvisation in ragtime and choro
Keywords: ragtime; choro; improvisação; música popular brasileira; música popular norte-americana; ragtime; choro; improvisation; Brazilian popular music; North-American popular music